1990
DOI: 10.1152/jappl.1990.68.1.334
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of rat soleus muscle after 15 days of hindlimb suspension

Abstract: The properties of the contractile elements interacting to develop force in atrophied rat soleus muscle were studied by using single skinned fibers, which permitted direct access to the contractile apparatus. Muscle atrophy was induced by 15 days of hindlimb suspension. Suspension resulted in a decrease of maximal tension relative to an important decline in fiber diameter. Ca affinity of the contractile proteins was not changed insofar as the tension-pCa relationship was not shifted along the pCa axis. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 0 publications
1
30
0
3
Order By: Relevance
“…Muscle inactivity results in a transition from slow-oxidative toward a fast-glycolytic phenotype (Bigard et al, 1998;Hourde et al, 2005;Stevens et al, 1990), that affects both MHC and enzymes involved in metabolism. Conversely, controlled stimulation of a rapid-glycolytic muscle induces changes toward a slow-oxidative phenotype (Pette and Vrbova, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle inactivity results in a transition from slow-oxidative toward a fast-glycolytic phenotype (Bigard et al, 1998;Hourde et al, 2005;Stevens et al, 1990), that affects both MHC and enzymes involved in metabolism. Conversely, controlled stimulation of a rapid-glycolytic muscle induces changes toward a slow-oxidative phenotype (Pette and Vrbova, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These transitions were associated with aerobic-oxidative to glycolytic metabolic changes (32) that involved both variations in the glucose metabolism and phosphorylation/dephosphorylation events (33,34). Moreover, HU applied for 14 days on the slow-twitch antigravitational soleus caused an atrophy and a decrease in calcium sensitivity of skinned fibers (35). As previously mentioned, UDP-GlcNAc has been demonstrated to be sensitive to glucose levels; moreover, correlations between the glycogen content and the O-GlcNAc level have been measured in skeletal muscle (36).…”
mentioning
confidence: 99%
“…If atrophy is the primary underlying mechanism to explain hindlimb unweighted induced decline in force generating capacity, there would be no change in specific tension. In previous studies specific tension is reduced suggesting that atrophy is only a part of the explanation for unweighting induced reduction in force (Alley and Thompson, 1997;Fitts et al, 2001;Sandmann et al, 1998;Stevens et al, 1990). In the current study, there is also a significant decrease in specific tension with hindlimb unweighting in the young and very old as the diameter and force do not decrease proportionately.…”
Section: Treadmill Exercise Induced Changesmentioning
confidence: 93%
“…The increased ATPase activity was attributed to the non-weight bearing-induced increase in the SERCA1 (fast) isoform expression in the soleus (Peters et al, 1999;Schulte et al, 1993). After 15 days of hindlimb unweighting Stevens et al, (1990) also showed increased calcium uptake and release by the SR in the soleus muscle that functionally were comparable to fast muscle. Calcium release from the SR is regulated by the voltagesensitive dihydropuridine receptor, which triggers the release of SR calcium by the ryanodine receptors.…”
Section: Non-weight Bearing Induced Changesmentioning
confidence: 96%
See 1 more Smart Citation